From coexistence to dominance in lung cancer surgery - Kang, Chang Hyun (Video-Assisted Thoracic Surgery; Vol 1 (August 2016): Video-Assisted Thoracic Surgery, 2016)
All surgical procedures are accompanied by surgical damage to the diseased patient. The adverse effects of surgical damage can be caused by resection of target organs, surgical approaches, or perioperative interventions. Reducing surgical damage and enhancing early recovery of patients is an important issue in improving the quality of surgical treatments. The concept of minimally invasive surgery which results in minimum damage to tissue or organs of patients is not a new one at all. Video-assisted thoracic surgery (VATS) is a dominant form of minimally invasive surgery in lung cancer. It was introduced decades ago and is now a routine daily procedure in lung cancer surgery.